Current status and needs of in-service training for psychiatric nurses in 24 provinces of China: a cross-sectional survey - Tan, Xiaolin; Pan, Minghao; Wan, Zhiying; Yang, Ying; Zhang, Lijuan; Fang, Yu; Li, Xiaofen; Shen, Meiyu (Frontiers in Psychology, 2024)
Aim To investigate the current situation and need for post-competence training for psychiatric nurses in China and provide a reference for the development of training programs for psychiatric nurses. Design A cross-sectional design. Methods A cross-sectional study was conducted from August to October 2023 with 435 psychiatric nurses from 34 hospitals in 24 provinces of mainland China. A self-administered questionnaire was used for data collection. Descriptive statistics, non-parametric tests, and chi-square tests were used for data analysis. Results The training content for psychiatric nurses is extensive, and the training load is large. Psychiatric nurses have high training demands for first aid knowledge, emergency handling ability, and anti-riot skills. Nurses with different years of experience have different training needs. The training needs of psychiatric nurses in specialized and general hospitals also different. Conclusion The training status of psychiatric nurses is not consistent with the demand. Managers should combine this with psychiatric nurses’ own work needs to develop practical and effective training programs.